2013
DOI: 10.3109/10826084.2013.824476
|View full text |Cite
|
Sign up to set email alerts
|

Do Importance of Religious Faith and Healthy Lifestyle Modify the Relationships Between Depressive Symptoms and Four Indicators of Alcohol Consumption? A Survey of Students Across Seven Universities in England, Wales, and Northern Ireland

Abstract: We examined the associations between depressive symptoms and four indicators of alcohol consumption (high frequency of drinking, frequency of heavy episodic drinking, problem drinking, and possible alcohol dependence). We also explored whether personal importance of religious faith as well as healthy lifestyle had any modifying roles in these relationships. During 2007-2008, 3,220 students at seven UK universities completed a questionnaire containing questions on CAGE, frequency alcohol use, heavy episodic dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 63 publications
(64 reference statements)
3
24
0
1
Order By: Relevance
“…Others [86] found significant relationships between monthly income and being ever substance user but undertook only bivariate analysis, not controlling for a range of factors. Finally, our finding that lower levels of religiosity were associated with higher likelihood of engagement in four alcohol behaviors agrees with that religiosity was negatively associated with frequency of drinking and HED among both genders [56]. Religiosity is a factor associated with the protection of individuals against alcohol consumption [87][88][89].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Others [86] found significant relationships between monthly income and being ever substance user but undertook only bivariate analysis, not controlling for a range of factors. Finally, our finding that lower levels of religiosity were associated with higher likelihood of engagement in four alcohol behaviors agrees with that religiosity was negatively associated with frequency of drinking and HED among both genders [56]. Religiosity is a factor associated with the protection of individuals against alcohol consumption [87][88][89].…”
Section: Discussionsupporting
confidence: 72%
“…The Health and Wellbeing Questionnaire employed in student health and wellbeing surveys. The tool was used and field-tested among university student populations across many countries [7,38,42,48,[56][57][58][59]. The questionnaire included sociodemographic information (e.g., sex age, marital status, parental education, accommodation during university terms, income sufficiency, and religiosity, i.e., importance of religious faith), academic related questions (e.g., year and discipline of study at university, importance of achieving good grades, and academic performance compared to peers), as well as self-reported health behavior data (e.g., five alcohol consumption behaviors, HED, problem drinking, and possible alcohol dependence).…”
Section: Health and Wellbeing Questionnairementioning
confidence: 99%
“…Ruiz, González, Vera, & Azancot, (2011) also found that religion can act as a protective factor among the university population against health and nutritional behaviour and habits. Similar results have been described in other countries with a university population of different religious denominations (El Ansari, Sebena & Stock, 2014;Neighbors et al, 2013). However Tanton, Dodd, Woodfield, & Mabhala, (2015) found different result.…”
Section: Discussionsupporting
confidence: 83%
“…The scope of the current research is in line with other general student health and wellbeing surveys undertaken in a number of countries [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 88%